How do small and medium-sized enterprises learn through collaborative networks for innovation? A mixed methodology to explore absorptive capacity supporting learning. (31st January 2023) - Ayala, Néstor Fabián; Le-Dain, Marie Anne; Benhayoun-Sadafiyine, Lamiae; Marcon, Arthur; Dominguez-Péry, Carine
This study investigates how an SME learns in a collaborative network for innovation (CNI) context by deploying absorptive capacity (ACAP) practices. More specifically, we explore the effects of ACAP practices for reciprocal learning upon those used for one-way learning throughout the network creation and operation stages. To hypothesise these effects, we relied on prior literature and empirical evidence drawn from interviews with 13 SMEs embedded in three different CNIs. We then used PLS regression to test these hypotheses based on data collected from 74 SMEs. Results show that ACAP for reciprocal learning has different effects on ACAP for one-way learning, depending on the network stage. This study provides a better understanding of the development of both learnings throughout a CNI. It also raises practitioners' awareness of the most important aspects of ACAP for deriving valuable learnings from their network experiences.